Random Loads Fatigue. Experimental Approach through Thermoelasticity. (2015) - Braccesi, Claudio; Cianetti, Filippo; Moretti, Michele; Rossi, Gianluca
Abstract: The aims achieved in this work have been the development of a software for the processing of thermal imaging films in frequency domain which makes the use of the thermovision useful to the assessment of the fatigue damageability of components loaded by random loads conditions. To this aim an experimental test rig and the relative measuring chain was built. The measuring system allows to analyze a system or a mechanical component providing the user, in addition to the usual thermographic output, a whole series of results of both local and global type.